Validation of an optimised protocol for quantification of microplastics in heterogenous samples: A case study using green turtle chyme - Alexandra G.M. Caron; Colette R. Thomas; Kathryn L.E. Berry; Cherie A. Motti; Ellen Ariel; Jon E. Brodie (MethodsX, 2018)
Quantifying the extent of microplastic (<5 mm) contamination in the marine environment is an emerging field of study. Reliable extraction of microplastics from the gastro-intestinal content of marine organisms is crucial to evaluate microplastic contamination in marine fauna. Extraction protocols and variations thereof have been reported, however, these have mostly focussed on relatively homogenous samples (i.e. water, sediment, etc.). Here, we present a microplastic extraction protocol for examining green turtle (Chelonia mydas) chyme (i.e. ingested material and digestive tract fluid), which is a heterogeneous composite of various organic dietary items (e.g. seagrass, jellyfish) and incidentally-ingested inorganic materials (sediment). Established extraction methods were modified and combined. This protocol consists of acid digestion of organic matter, emulsification of residual fat, density separation from sediment, and chemical identification by Fourier transform-infrared spectroscopy. This protocol enables the extraction of the most common microplastic contaminants>100 μm: polyethylene, high-density polyethylene, (aminoethyl) polystyrene, polypropylene, and polyvinyl chloride, with 100% efficiency. This validated protocol will enable researchers worldwide to quantify microplastic contamination in turtles in a reliable and comparable way. • Optimization of microplastic extraction from multifarious tissues by applying established methods in a sequential manner. • Effective for heterogenous samples comprising organic and inorganic material. Method name: Sequential protocol for extracting microplastics from heterogenous sample matrices, Keywords: Plastic ingestion, Marine debris, Plastic contamination, Extraction technique, Chemical digestion, Density separation, Fourier transform-infrared spectroscopy